A new species of the genus Hebius (Squamata: Colubridae) from Sichuan, China - Liu, Qin; Zhong, Guang-Hui; Wang, Ping; Liu, Yang; Guo, Peng (Zootaxa, 2018)
A new species of the natricine snake genus Hebius Thompson, 1913 is described from Sichuan Province, Southwest China, based on a single male specimen. The new species is distinguished from its congeners found in China and adjacent regions by possessing the following combination of characters: 1) TL/SVL ratio 0.35; 2) three postoculars; 3) six temporals in formula 1/(1+1) +1+2; 4) eight supralabials, 4th and 5th in contact with the eye, 6th supralabial largest; 5) ten infralabials with the first five bordering the anterior chinshields; 6) 172 ventrals (plus two preventrals); 7) cloacal plate divided; 8) 90 divided subcaudals; 9) dorsal scales in 19-19-17 rows, all weakly keeled except the outer two; 10) reduction of dorsal scale rows from 19 to 17 at the position above ventral scale 99th; 11) reduction of the tail dorsal scales from 8 to 6 rows at the position above 18th subcaudal, and from 6 to 4 rows at the position above 37th subcaudal; 12) postorbital bones do not touch frontals, the parietal ridge weakly developed; the end of the supratemporal bones extending beyond the braincase; maxillary teeth 23–25, the last two enlarged, without diastema between them and the anterior teeth. This species is an evergreen forest dweller.